Track Dating Hadith Fly Wings: A Study of Harald Motzki’s Isnad cum Matn Method and Science - Mufid, Abdul; Sattar, Abdul; Rifai, Idris Ahmad (UIN Sunan Kalijaga Yogyakarta, 2023)
This study explored and analyzed fly wings from the perspectives of hadith and science. It used a qualitative, analytical descriptive approach and integrated Harald Motzki's Isnad Cum Matn analysis with pharmaceutical studies. The research question was: How do hadith and pharmacy view fly wings? The results showed that 21 hadith books mention fly wings, including Sahih Bukhari. The hadith of the fly wings is valid, with Utbah bin Muslim as the common link (disseminator of hadith). From the perspective of pharmaceutical science, most microorganisms on flies, such as germs, viruses, and microbes, can cause diseases. However, drowning flies can neutralize these microorganisms against the fluid they perceive. This shows that science is in harmony with the hadith of the Prophet.